TprA/PhrA Quorum Sensing System Has a Major Effect on Pneumococcal Survival in Respiratory Tract and Blood, and Its Activity Is Controlled by CcpA and GlnR - Anfal Shakir Motib; Anfal Shakir Motib; Firas A. Y. Al-Bayati; Firas A. Y. Al-Bayati; Irfan Manzoor; Sulman Shafeeq; Anagha Kadam; Oscar P. Kuipers; N. Luisa Hiller; Peter W. Andrew; Hasan Yesilkaya (Frontiers in Cellular and Infection Microbiology, 2019)
Streptococcus pneumoniae is able to cause deadly diseases by infecting different tissues, each with distinct environmental and nutritional compositions. We hypothesize that the adaptive capabilities of the microbe is an important facet of pneumococcal survival in fluctuating host environments. Quorum-sensing (QS) mechanisms are pivotal for microbial host adaptation. We previously demonstrated that the TprA/PhrA QS system is required for pneumococcal utilization of galactose and mannose, neuraminidase activity, and virulence. We also showed that the system can be modulated by using linear molecularly imprinted polymers. Due to being a drugable target, we further studied the operation of this QS system in S. pneumoniae. We found that TprA controls the expression of nine different operons on galactose and mannose. Our data revealed that TprA expression is modulated by a complex regulatory network, where the master regulators CcpA and GlnR are involved in a sugar dependent manner. Mutants in the TprA/PhrA system are highly attenuated in their survival in nasopharynx and lungs after intranasal infection, and growth in blood after intravenous infection.